Political ideas, values and ideology: a study of the Conservative Party views on education 1944-1966 - Shaw, Stephen (1980)
This thesis is a study of Conservative Party views on education during the period 1944-1966, and, in particular, it considers the extent to which a ‘conservative ideology’ is implicit in Conservative attitudes and policies.